Structural and Functional Characterization of Recombinant Interleukin-10 from Indian Major Carp Labeo rohita - Sweta Karan; Pujarini Dash; Himani Kaushik; Pramoda K. Sahoo; Lalit C. Garg; Aparna Dixit (Journal of Immunology Research)
Interleukin-10, an important regulator of both the innate and adaptive immune systems, is a multifunctional major cytokine. Though it is one of the major cytokines, IL-10 from the Indian major carp, Labeo rohita, has not yet been characterized. In the present study, we report large scale production and purification of biologically active recombinant IL-10 of L. rohita (rLrIL-10) using a heterologous expression system and its biophysical and functional characterization. High yield (~70 mg/L) of soluble rLrIL-10 was obtained at shake flask level. The rLrIL-10 was found to exist as a dimer. Far-UV CD spectroscopy showed presence of predominantly alpha helices. The tertiary structure of the purified rLrIL-10 was verified by fluorescence spectroscopy. Two-dimensional gel analysis revealed the presence of six isoforms of the rLrIL-10. The rLrIL-10 was biologically active and its administration significantly reduced serum proinflammatory cytokines, namely, interleukin 1β, TNFα, and IL-8, and augmented the NKEF transcript levels in spleen of L. rohita. Anti-inflammatory role of the rLrIL-10 was further established by inhibition of phagocytosis using NBT reduction assay in vitro. The data indicate that the dimeric alpha helical structure and function of IL-10 of L. rohita as a key regulator of anti-inflammatory response have remained conserved during evolution.